Duplikasi Fungsi Dokumen Proposal Inisiatif Baru dan Dokumen Kerangka Acuan Kerja - Irwan Suliantoro (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2021)
New Initiatives are proposals for additional performance plans in the form of new programs, activities, outputs. New Initiative proposals are addressed to Bappenas through the New Initiative document and the Directorate General of Budget (DG Budget) through the Terms of Reference (TOR) document. There is a duplication of functions between the New Initiative document (Bappenas version) and the TOR document (DG Budget version). Both documents contain information about the substance of the new output. The similarities in substance in the two documents include the proposed organizational entity, proposed new output, target output volume, output indicators, background, beneficiaries, and proposed budgets up to the component level. From the bureaucratic side, the duplication of functions, among others, creates inefficiency in the bureaucratic process and creates an impression of a lack of consistency between policies in the planning and budgeting domains. It should be reduced. The mechanism for proposing proposals for New Initiatives needs to be integrated with the TOR concept. Integration is carried out by compiling documents and issuing regulations under a common legal umbrella between Bappenas and the Ministry of Finance. Keyword: New Initiative, Term of Reference Â